2011
DOI: 10.1074/jbc.m110.190108
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Mapping of Reversible Mitochondrial Complex I Cysteine Oxidation in a Parkinson Disease Mouse Model

Abstract: Differential cysteine oxidation within mitochondrial Complex I has been quantified in an in vivo oxidative stress model of Parkinson disease. We developed a strategy that incorporates rapid and efficient immunoaffinity purification of Complex I followed by differential alkylation and quantitative detection using sensitive mass spectrometry techniques. This method allowed us to quantify the reversible cysteine oxidation status of 34 distinct cysteine residues out of a total 130 present in murine Complex I. Six … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 38 publications
0
43
0
Order By: Relevance
“…MnTBAP restored the protein levels of representative subunits of mitochondrial OXPHOS complexes I and III in UCP-DTA hearts. These complexes are the main sites of mitochondrial ROS generation [41], and the damage to specific subunits or iron-sulfur clusters may make them susceptible to oxidative damage and degradation or improper assembly [42]. Reduced expression of mitochondrial OXPHOS complex I, mitochondrial dysfunction and overflow of ROS was previously documented in the hearts and skeletal muscle of insulin resistant and obese mice and humans, respectively [4, 43].…”
Section: Discussionmentioning
confidence: 99%
“…MnTBAP restored the protein levels of representative subunits of mitochondrial OXPHOS complexes I and III in UCP-DTA hearts. These complexes are the main sites of mitochondrial ROS generation [41], and the damage to specific subunits or iron-sulfur clusters may make them susceptible to oxidative damage and degradation or improper assembly [42]. Reduced expression of mitochondrial OXPHOS complex I, mitochondrial dysfunction and overflow of ROS was previously documented in the hearts and skeletal muscle of insulin resistant and obese mice and humans, respectively [4, 43].…”
Section: Discussionmentioning
confidence: 99%
“…In dopaminergic neurons and model cells, oxidative and nitrosative stress causes preferential inhibition of complex I activity and extensive accumulation of S-nitrosothiols in mitochondrial proteins, with many modifications occurring in complex I (55,67,71). A recent proteomics study in an animal model of PD identified 34 distinct cysteine residues in the components of complex I (26% of total thiol groups), which are modified during disease progression in vivo (68). S-nitrosating compounds, such as S-nitroso-l-cysteine, strongly inhibit mitochondrial O 2 consumption and ATP production in isolated brain nerve endings (synaptosomes) and in neuronal cells (34,81,222).…”
Section: The Mitochondrial Electron Transport Chainmentioning
confidence: 99%
“…52,53 The degree to which this process can affect protein activity, varies according to the role and importance of the cysteine residue for carrying out protein function, regardless of glutathione, but still under reversible redox control or, alternatively, as a result of oxidative damage. 54,55 Thus, Meth as a ROS-inducer and trigger, and NAC as a controller, can potentially be acting on the same residues, but in different ways. BAT is a tissue that may be particularly sensitive to such mechanism, for being a high redox environment with a high mitochondrial content.…”
Section: Discussionmentioning
confidence: 99%